Porphyrin-Based Organoplatinum(II) Metallacycles With Enhanced Photooxidization Reactivity - Wu, Lintao; Han, Chun; Wang, Zhijun; Wu, Xi; Su, Feng; Li, Mengyao; Zhang, Qingyang; Jing, Xiaobi (Frontiers in Chemistry, 2020)
In recent years, metal coordination macrocycles have obtained great interests due to the fact that they combined the rich host-guest properties of macro-cyclic hosts and the unique optical properties of the organic ligands. In this work, we constructed two porphyrin-based organoplatinum(II) metallacycles (MC1 and MC2) through coordination-driven self-assembly. 1H NMR, 31P NMR, and HRMS technologies were used to characterize the structures of MC1 and MC2. Interestingly, MC1 and MC2 can be used as catalysts for photooxidization under light irradiation with higher efficiency compared with the porphyrin ligand only. We hope that the coordination-driven self-assembly strategy can provide an efficient method to construct photo-active materials.